Hydrochemical Characterization and Assessment of Groundwater Quality in the Mining Environment of Afema Township (South-East of Côte d’Ivoire) - Kouadio Assemien François Yao; Kouassi Ernest Ahoussi; Yao Blaise Koffi; Lou Moin Sandrine Tivoli; David Salze; Miguel Lopez-Ferber (European Scientific Journal, ESJ, 2023)
Afema Township, located in the department of Aboisso, was mined from 1992 to 1998. At the end of the exploitation, the sites did not undergo any real rehabilitation work. In order to determine the impact of these mining activities on the physicochemical characteristics and quality of groundwater, this study was undertaken. The results of the water analyses collected in the mining area were processed using Piper's triangular diagram and Principal Component Analysis (PCA). The methodological approach consisted, first of all, in determining the hydro-facies of the waters studied, then in dividing them into different groups on the basis of their hydro-chemical similarity and in identifying the factors likely to explain both the origin of the parameters studied and their correlation. Finally, the overall quality of these waters was estimated from the calculation of the quality index. The results showed that the waters studied were divided into two main families: chloride-calcium-magnesium waters and bicarbonate-calcium-magnesium waters. They were on the whole weakly mineralized, with an average electrical conductivity of 195.76 μS.cm-1. This mineralization was controlled by two essential phenomena, the residence time of water in the aquifers and surface infiltration and leaching from unsaturated ground. The physico-chemical quality of the groundwater studied complied with the standards of potability recommended by the WHO. However, the results also showed high levels of cadmium (0.052 mg.L-1) and lead (0.058 mg.L-1); this explained the overall poor quality of these waters according to the water quality index. Thus, the studied waters presented a real risk for human consumption. The consumption of these waters by local communities exposes them to health risks.